2019
DOI: 10.3390/rs11192242
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Smartphone SfM Photogrammetry to Measure Coastal Morphodynamics

Abstract: With recent advances in photogrammetric processing methods and sensor technologies, smartphones represent a new opportunity of mainstream, low-cost sensor, with a great potential for Structure-from-Motion (SfM) photogrammetry, and in particular for participatory science programs or citizen observatories. Keeping in mind the application in citizen observatories, three smartphone models (Galaxy S7®, Lumia 930® and iPhone 8®) and a bridge camera were compared (separately and in combination) for coastal applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
(9 reference statements)
0
19
0
4
Order By: Relevance
“…For measuring the entire cliff face, the setup was moved to different camera stations. For each station, approximately five to ten photographs are collected according to a "fan-shaped capture" (i.e., spinning the camera around the vertical axis [9]) and the station position is measured by RTK GNSS For measuring the entire cliff face, the setup was moved to different camera stations. For each station, approximately five to ten photographs are collected according to a "fan-shaped capture" (i.e., spinning the camera around the vertical axis [9]) and the station position is measured by RTK GNSS using a 30-s average.…”
Section: Survey Operational Modementioning
confidence: 99%
See 1 more Smart Citation
“…For measuring the entire cliff face, the setup was moved to different camera stations. For each station, approximately five to ten photographs are collected according to a "fan-shaped capture" (i.e., spinning the camera around the vertical axis [9]) and the station position is measured by RTK GNSS For measuring the entire cliff face, the setup was moved to different camera stations. For each station, approximately five to ten photographs are collected according to a "fan-shaped capture" (i.e., spinning the camera around the vertical axis [9]) and the station position is measured by RTK GNSS using a 30-s average.…”
Section: Survey Operational Modementioning
confidence: 99%
“…Aerial surveys are generally performed by Unmanned Aerial Vehicles (UAVs) and mainly used for beach surveys [1][2][3], whereas data collected from a terrestrial point of view are more suited to cliff surveys, allowing for better capturing the cliff face. These terrestrial data are typically obtained using a Terrestrial Laser Scanner (TLS) [4,5], a Mobile Laser Scanner (MLS) [6,7], or terrestrial photogrammetry [8,9]. This article focuses more particularly on these terrestrial methods.…”
Section: Introductionmentioning
confidence: 99%
“…Four point cloud comparison methods are commonly used to compare 3D point clouds: DEM of difference (DoD) [53][54][55][56], cloud-to-cloud (C2C) distance [57][58][59][60], C2M distance [47,[61][62][63], and M3C2 distance [64][65][66][67][68][69]. The DoD approach subtracts two DEMs or DSMs using a top view and is fast/easy to implement and interpret.…”
Section: Derived Products Comparisonmentioning
confidence: 99%
“…The results showed that properly calibrated smartphone cameras can be used for photogrammetric tasks with a required accuracy of 1:10,000. The smartphone SfM photogrammetric method has been tested in many fields including flexible structural monitoring [ 18 ], coastal monitoring [ 19 , 20 , 21 ], auxiliary medical examinations [ 22 , 23 ], alpine alluvial fan surveys [ 24 ], and soil water erosion [ 25 ]. Although the smartphone SfM photogrammetric method has been successfully used in these applications and has produced high-resolution results, to the best of the authors’ knowledge, this approach has rarely been used for mapping the topography of rock joint surfaces in geotechnical laboratories.…”
Section: Introductionmentioning
confidence: 99%